A cinnamaldehyde-based formulation as an alternative to sodium hypochlorite for post-harvest decontamination of citrus fruit - Zamuner, Caio F. C. [UNESP]; Dilarri, Guilherme [UNESP]; Bonci, Lucia C. [UNESP]; Saldanha, Luiz L. [UNESP]; Behlau, Franklin; Marin, Tamiris G. S.; Sass, Daiane C. [UNESP]; Bacci Jr, Mauricio [UNESP]; Ferreira, Henrique [UNESP] (Springer, 2020)
According to the most recent regulation, published in 2018, areas or states of Brazil where citrus canker is endemic are no longer obliged to eradicate citrus trees affected by the disease as in the past 60 years. Instead, growers have to adopt a set of control measures, such as copper sprays, windbreaks, and control of the citrus leaf miner to minimize the impact of the disease on fruit quality and yield. Another important change was that all fresh Fruit commercialized out of the state of origin and to other countries have to be sanitized against the canker-causing bacterium Xanthomonas citri subsp. citri (X. citri). Initially, sodium hypochlorite (NaOCl) was the only product allowed in Brazil by the referred legislation. Recently, this bactericide was prohibited to be used on fresh fruit shipped to the European Union and replaced by eugenol at 2%. Although effective, NaOCl may damage fruit skin, cause corrosion of packing house equipment and react with organic matter, which generates noxious by products. Here, we evaluated an alternative to NaOCl known as PosFruit. GC/MS and H-1 NMR chemical analyses showed that Posfruit contains both cinnamaldehyde isomers, with the trans being present in larger quantities. We showed that PosFruit was as effective as NaOCl to eliminate X. citri from citrus fruit artificially contaminated with the bacterium. In a pilot sanitization line, treatment with 2% PosFruit reduced the X. citri population on contaminated fruit by 4 log(10) CFU/mL. Furthermore, we detect neither the natural resistance of X. citri to PosFruit nor the persistence of the bacterium following progressive exposure to the product, which indicates that the product has multi-target action. PosFruit is a plant fortifier, residue-free, and efficient alternative to NaOCl for post-harvest decontamination of citrus fruit against X. citri.
Keywords: Citrus canker; Fresh fruit; Sanitization